A new species of Epopostruma (Hymenoptera: Formicidae) from monsoonal Australia - Pettit, Magen J.; Andersen, Alan N. (Zootaxa, 2021)
Epopostruma is an uncommon genus of myrmicine ants endemic to relatively mesic regions of southern and eastern Australia. Here we describe a new species recently recorded from the ‘Top End’ of Australia’s Northern Territory, E. topendi sp. n. from Melville Island and Nitmiluk National Park. The new species is known from one specimen from each of two sites in the Australian monsoonal tropics, the only records of the genus from this region. This addition brings the number of described species of Epopostruma to twenty.